Cosmopolitan polychaete species: the status of Aricidea belgicae (Fauvel, 1936) and notes on the identity of A. suecica Eliason, 1920 (Polychaeta; Paraonidae). - Hartley, John P. (1984)
Following an examination of the type specimen and material from a variety of locations it was concluded that few published records of Aricidea beigicae (Fauvel, 1936) actually refer to this species. A. belgicae is redescribed, previous records are reassigned where possible and two new species, Aricidea roberti n. sp. and Aricidea bulbosa n. sp. are described from the northern North Sea and Gulf of Suez respectively. Similarly an examination of specimens of Aricidea spp. from a large number of localities around Britain and the North Sea indicates that Aricidea suecica Eliason, 1920 is restricted to estuarine and coastal waters, being replaced by other species in deeper water. Since A. suecica has been recorded as eurybathic and worldwide in distribution it is believed that the majority of records require confirmation. To this end a detailed description of A. suecica is presented. Consideration is given to the causes of the taxonomic uncertainty which has led to A. belgicae and A. suecica being regarded as cosmopolitan species. The most important causes are believed to be a reliance on old descriptions and drawings in which insufficient attention was given to characters now regarded as being of specific importance, and the identification of fragmented specimens from which diagnostic characters are missing.
World Polychaeta Database (WPolyD)